PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN KECERDASAN SPIRITUAL TERHADAP PRESTASI BELAJAR MATA PELAJARAN EKONOMI PADA PESERTA DIDIK KELAS XI IPS DI SMA NEGERI 1 BULU TAHUN AJARAN 2017/2018 - -, Rizky Sulastyaningrum -; -, Trisno Martono -; -, Budi Wahyono - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The aims of this research are: 1) to determine the influence of intelligence quotient toward the learning achievement of economics in class XI of SMA Negeri 1 Bulu, 2) to determine the influence of emotional quotient toward the learning achievement of economics in class XI of SMA Negeri 1 Bulu, 3) to determine the influence of spiritual quotient toward the learning achievement of economics in class XI of SMA Negeri 1 Bulu, and 4) to determine simultaneous the influence of intelligence quotient, emotional quotient, and spiritual quotient toward the learning achievement of economics in class XI of SMA Negeri 1 Bulu. This research is a quantitive research. The population of the research was class XI in SMA Negeri 1 Bulu in the academic year 2017/2018 as many as 4 classes with a total 151 students. The sampling technique used was probability random sampling. The number of samples was 110 respondents. The data collection methods use were documentation, test, and questionnaire. The data analysis technique used was multiple linier regression.The result of the research shows that the equity of the multiple regression is Y = 37.909 + 1.612 X1 + 0.123 X2 + 0.107 X3. The regression coefficient is positive which means that intelligence quotient, emotional quotient, and spiritual quotient is positively and significantly influential toward the learning achievement of the students. It means that the higher intelligence quotient, emotional quotient, and spiritual quotient is the higher the student?s learning achievement will be. Based on the result of the research, it can be conclude that: (1) intelligence quotient is positively and significantly influential toward the learning achievement of the students which is shown by the probability value of <0,05 (0.000<0.005), (2) emotional quotient is positively and significantly influential toward the learning achievement of the students which is shown by the probability value of <0,05 (0.044<0.005), (3) spiritual quotient is positively and significantly influential toward the learning achievement of the students which is shown by the probability value of <0,05 (0.046<0.005), and (4) intelligence quotient, emotional quotient, and spiritual quotient is positively and significantly influential toward the learning achievement of the students which is shown by the probability value of <0,05 (0.000<0.005). Adjusted R Square value is 78%, it shown that 78% of the learning achievement of the students is influenced by intelligence quotient, emotional quotient, and spiritual quotient, while the rest which is 22% is influenced by other factors not mentioned in this research.